Chiral Photoresponsive Liquid Crystalline Materials Derived from Cyanoazobenzene Central Core: Effect of UV Light Illumination on Mesomorphic Behavior - Anna Poryvai (Crystals, 2020)
One of the most frequently utilized liquid crystalline (LC) materials is a rod-like (calamitic) compound 4-cyano-4′-pentylbiphenyl (5-CB). The main objective of this work is to enhance its functionality by introducing a photoresponsive diazenyl spacer in the aromatic core and replace the non-chiral pentyl chain with various chiral alkyl carboxylate units. The mesomorphic properties of the prepared materials have been studied using polarizing optical microscopy and differential scanning calorimetry. It has been found that materials with an extended aromatic system possess the liquid crystalline behavior. The studied LC materials have shown mesophases at lower temperatures than previously reported analogous substances. Furthermore, one of them exhibits a chiral orthogonal frustrated twist grain boundary smectic phase, which has not been previously observed for this structural type of materials. We also investigated photoresponse of the mesophases under illumination with UV-light (365 nm) using a polarizing optical microscope. A non-conventional photoresponse of the prepared materials in a crystalline phase is presented and discussed.